Pyridoxine dependent epilepsy: Is late onset a predictor for favorable outcome?. (July 2018) - de Rooy, R.L.P.; Halbertsma, F.J.; Struijs, E.A.; van Spronsen, F.J.; Lunsing, R.J.; Schippers, H.M.; van Hasselt, P.M.; Plecko, B.; Wohlrab, G.; Whalen, S.; Benoist, J.F.; Valence, S.; et al.
Abstract: Aim: In pyridoxine dependent epilepsy (PDE), patients usually present with neonatal seizures. A small subgroup is characterized by late-onset beyond 2 months of age. We aim to analyze the observation of relatively good cognitive outcome in this subgroup of late-onset PDE patients. Methods: We retrospectively analyzed data from four metabolically and genetically confirmed late-onset patients with PDE due to antiquitin (ALDH7A1) deficiency. Data were analyzed regarding ALDH7A1 mutations, alpha-Aminoadipic semialdehyde (α-AASA) and pipecolic acid (PA) levels, medication during pregnancy, delivery, treatment delay, amount of seizures, pyridoxine dose, adjuvant therapy and findings on brain MRI. Results: Results showed that three patients had relatively good outcome (IQ 80–97), while one patient did not undergo formal testing and was considered mildly delayed. We were unable to find a clear association between the above-mentioned variables and cognitive outcome, although a less severe genotype may be present in three patients, and maternal medication could be accountable for better outcome in two patients. Interpretation: We suggest that favorable outcome in late onset PDE might be explained by a combination of factors. A yet unknown protective factor, different genetic variations, functional variation and secondarily variation in treatment regimens and absence of neonatal seizure induced brain damage. Highlights: In late onset PDE, IQ tends to be higher than in the majority of classic early onset PDE. In comparison with reported cases, no obvious explanation for the mild outcome in our four late onset PDE patients could be found. The prolonged absence of seizures might play a role, metabolic factors as lower AASA and PA levels as well. A less severe genotype–phenotype correlation might account to mild outcome in three out of four patients. Adjuvant therapy and folic acid substitution during pregnancy might be preventive.